'Can we have a child exchange?' Constructing and subverting the 'good mother' through play in Mumsnet Talk. (May 2017) - Mackenzie, Jai
This article uses a feminist poststructuralist approach to explore how contributors to a single thread from the discussion forum of a popular British parenting website, Mumsnet Talk, position themselves as 'good mothers'. The qualitative analysis that is presented here, which draws on both the concept of indexicality and Goffman's 'frame analysis', shows that Mumsnet users are able to negotiate the discursive forces that merge to produce the good mother subject position in innovative ways. They are able to position themselves as good mothers in a way that is both normative and transformative – to both legitimise and subvert the discourses that work to position them in this way. This exploration leads me to suggest that the Mumsnet Talk forum can be seen as a space in which dominant discourses continue to position individuals in restricted gendered subjectivities, but is also a fruitful site for the negotiation, resistance and subversion of cultural norms.